Peripheral Interleukin-1β Levels are Elevated in Chronic Tension-Type Headache Patients - Chris Della Vedova; Stuart Cathcart; Alan Dohnalek; Vanessa Lee; Mark R Hutchinson; Maarten A Immink; John Hayball (Pain Research and Management)
BACKGROUND: Tension-type headache is the most common form of headache and its chronic form, chronic tension-type headache (CTTH), is one of the most difficult to treat. The etiology of CTTH is not well understood, but is believed to be multifactorial and to vary among individuals. In the present study, the authors sought to identify common mechanisms of CTTH pathology. Empirical studies have implicated various immunomodulatory cytokines as mediators of chronic pain disorders, including CTTH.